2004
DOI: 10.1016/j.femsle.2004.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Gram-positive bacteria to nisin is not determined by Lipid II levels

Abstract: Lipid II is essential for nisin-mediated pore formation at nano-molar concentrations. We tested whether nisin resistance could result from different Lipid II levels, by comparing the maximal Lipid II pool in Micrococcus flavus (sensitive) and Listeria monocytogenes (relatively insensitive) and their nisin-resistant variants, with a newly developed method. No correlation was observed between the maximal Lipid II pool and nisin sensitivity, as was further corroborated by using spheroplasts of nisin-resistant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 26 publications
(35 reference statements)
3
94
0
Order By: Relevance
“…Total viable population (TVC) was significantly (P < 0.05) lower in nisin containing yoghurt than those without nisin [46,47]. No significant difference (P > 0.05) in counts of yeast and mould and proteolytic organisms in yoghurt up to 30 and 20 days, respectively were encountered due to application of nisin.…”
Section: Effect Of Nisin On Microbiological Attributes Of Stirred Yogmentioning
confidence: 93%
“…Total viable population (TVC) was significantly (P < 0.05) lower in nisin containing yoghurt than those without nisin [46,47]. No significant difference (P > 0.05) in counts of yeast and mould and proteolytic organisms in yoghurt up to 30 and 20 days, respectively were encountered due to application of nisin.…”
Section: Effect Of Nisin On Microbiological Attributes Of Stirred Yogmentioning
confidence: 93%
“…Estimates for Gram-positive bacteria typically give values below 1 mol% of the membrane phospholipids [1]. This small amount of Lipid II is responsible for the fast growing bacterial cell wall.…”
Section: Lipid II Occurrence and Propertiesmentioning
confidence: 99%
“…In contrast, use of vancomycin, which also binds to Lipid II, but only to the terminal part of the pentapeptide, can result in resistance, because the bacteria can change the composition of the pentapeptide without interfering with cell wall synthesis, thereby blocking the vancomycin-Lipid II interaction and thus losing vancomycin sensitivity. Growing bacteria under pressure of increasing amounts of nisin can develop tolerance to nisin, which is not due to a change in amount or localization of Lipid II but is caused by changes in cell wall thickness and cell wall charge both shielding the plasma membrane from nisin [1].…”
Section: How Can Lantibiotics In Such a Versatile Manner Use Lipid IImentioning
confidence: 99%
“…It has been shown that many nisin-sensitive Grampositive bacteria, including clinically relevant strains, can acquire nisin resistance upon repeated exposure to increasing nisin concentrations [10,44,94,95]. This type of resistance is often lost once nisin pressure is removed [10] and is more accurately described as a physiological adaptation, although the nisin resistance of Streptococcus bovis was claimed to be stable, resistant cells were rapidly overgrown by sensitive ones [94]. Unlike vancomycin resistance, this adaptive mechanism does not involve an alteration of either the structure or quantity of lipid II.…”
Section: Lantibiotic-resistance Mechanismsmentioning
confidence: 99%
“…Despite the need for a continuous supply of lipid II, there exist approximately only 2000 intact molecules of this essential building block in a Gram-negative cell at any given time. This is likely due to the limited amount of C55 phospholipid (estimated to be 2 × 10 5 molecules per cell [10,11]) available for lipid II synthesis inside the cell and transport across the bacterial membrane. This suggests that the process by which lipid II is synthesized and incorporated into peptidoglycan is dynamic with respect to the C55 phopholipid (turnover rate for lipid II incorporation is estimated to be 1-3 transfers/sec/C55 phospholipid [12]).…”
mentioning
confidence: 99%